ANALISIS PENGARUH REPUTASI MEREK DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN PRODUK KIMIA FARMA PADA APOTEK DI KOTA MEDAN - , Aji Tetuko, S.Farm.; , Prof. Dr. Achmad Fudholi, DEA, Apt ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Customer loyalty due to the influence of satisfaction / dissatisfaction with the brand accumulated continuously. Some Kimia Farma products that sold at Medan in 2012 decreased by 6.78% compared to sales in 2011. The most customers PT Kimia Farma Trading & Distribution (KFTD) Medan is pharmacy,and the most Kimia Farma products are distributed in pharmacies. This study was conducted to analyze the influence of brand reputation and customer satisfaction, partially or jointly, to customer loyalty. This study followed the design of non-experimental survey at pharmacies in the city of Medan. Sampling was done by purposive sampling technique. Samples taken limited time from January to December 2012. The research subject is the customer who has authority to make purchases at the pharmacy, at least once each month in the interval between January to December 2012 through KFTD Medan. Variables used in this study consists of independent variables (brand reputation and customer satisfaction) and dependent variable (customer loyalty). Analysis is using multiple linear regression with SPSS 15. The samples used were 98 respondents. Majority of respondents or customers are women, aged 31-40 years, work assistant pharmacist, and graduated from high school. Testing the validity and reliability of the 32 respondents indicated that all items on the questionnaire proved to be valid and reliable questionnaire. Classical assumption test results showed normal distributed, no correlation occurred between the independent variables, and occurs homoskedastisitas between the independent variables. Results of multiple regression analysis: first, brand reputation and customer satisfaction together have a significant influences of 18.4% on customer loyalty Kimia Farma products at pharmacies in the city of Medan. Second, brand reputation has a positive and significant influence of 0,32 on customer loyalty Kimia Farma products at pharmacies in the city of Medan. Third, customer satisfaction has a positive and significant influence of 0,24 on customer loyalty Kimia Farma products at pharmacies in the city of Medan. This research result show that Kimia Farma require to evaluate the price so can more vie with other company.